Introduction: Feeding Bodies, Nurturing Identities: The Politics of Diet in Late Colonial and Early Post-Colonial India. Issue 1 (2nd January 2021) - Fischer-Tiné, Harald; Hauser, Julia; Malhotra, Ashok
Abstract: This introductory essay provides an overview of the main subfields of research into the histories of foodstuffs, diet and nutrition in nineteenth- and twentieth-century South Asia, thus situating the contributions to this themed special section in wider historiographical debates and controversies. It argues that the bulk of existing research has focused either on the conflictual role of food and diet in the colonial encounter, or on the emergence of nutritional sciences in India (and in the countries providing food aid to India) during the post-colonial phase in response to the protracted recurrence of food scarcity in the subcontinent. It subsequently identifies a research lacuna by pointing to the conspicuous absence of historical studies on Dalits and food in spite of the topic's obvious relevance for the creation and maintenance of social hierarchies. The article ends with short previews of the individual essays assembled in this collection.